Cost-effectiveness of palbociclib plus fulvestrant as second-line therapy of women with HR+/HER2- advanced breast cancer - A Chinese healthcare system perspective - Zhu, Wentao; Zheng, Miaomiao; Xia, Panpan; Hong, Wanglong; Ma, Guoqiang; Shen, Aizong (Frontiers in Oncology, 2023)
Aim: To evaluate the cost-effectiveness of palbociclib plus fulvestrant in the second-line treatment of women with hormone receptor-positive and human epidermal growth factor receptor 2-negative advanced breast cancer based on the latest published follow-up data from the perspective of the Chinese healthcare system. Methods: In view of the PALOMA-3 trial, a Markov model was built for this purpose, which included three health states: progression-free survival (PFS), progressed disease (PD), and death. The cost and health utilities were mainly derived from the published literature. One-way sensitivity analysis and probabilistic sensitivity analysis were carried out to verify the robustness of the model. Results: In the base case analysis, compared with the placebo arm, the palbociclib arm yielded an additional 0.65 quality-adjusted life years (QALYs) (2.56 QALYs vs. 1.90 QALYs) with an incremental cost of 36,139.94 (55,482.06 vs. 19,342.12), resulting an incremental cost-effectiveness ratio (ICER) of 55,224.90/QALY, which was deeply higher than a willingness-to-pay (WTP) threshold of 34,138.28 per QALY in China. The results of one-way sensitivity analysis indicated that the utility of PFS, cost of palbociclib, and cost of neutropenia had a great influence on the ICER. Conclusions: Palbociclib plus fulvestrant is unlikely to be cost-effective in comparison with placebo plus fulvestrant as second-line therapy of women with HR+/HER2- advanced breast cancer.